2009
DOI: 10.1017/s0950268809991312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clostridium difficile in dogs and the household environment

Abstract: Clostridium difficile may be an emerging community-associated pathogen but little is known about its sources of exposure. This study evaluated C. difficile contamination in households and colonization of pets. C. difficile was isolated from 44/836 (5.3%) sites in 26/84 (31%) households. Ribotype 027 was the most common (25%) environmental strain. C. difficile was isolated from 14/139 (10%) dogs. Living with an immunocompromised individual was associated with C. difficile colonization in dogs. All toxigenic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 19 publications
2
80
1
2
Order By: Relevance
“…All toxigenic strains identified in pets have been isolated from humans in Ontario, Canada. Although the prevalence of C. difficile in dogs and cats is low, the fact that all toxigenic strains are recognized human pathogens raises concern about interspecies transmission (205). Spores of C. difficile can also be detected in meat products and ready-to-eat salads (10,182,201,204), but there is no conclusive evidence that C. difficile contamination of food has led to clinical CDI in humans.…”
Section: Animals and Foods As Potential Sources Of C Difficilementioning
confidence: 99%
“…All toxigenic strains identified in pets have been isolated from humans in Ontario, Canada. Although the prevalence of C. difficile in dogs and cats is low, the fact that all toxigenic strains are recognized human pathogens raises concern about interspecies transmission (205). Spores of C. difficile can also be detected in meat products and ready-to-eat salads (10,182,201,204), but there is no conclusive evidence that C. difficile contamination of food has led to clinical CDI in humans.…”
Section: Animals and Foods As Potential Sources Of C Difficilementioning
confidence: 99%
“…C. difficile is widely recognized as a commensal and enteric pathogen in a wide range of host species (178)(179)(180). To date, C. difficile been recovered from numerous animal sources, including livestock (pigs, piglets, cows, calves, sheep, lambs, goats, and chickens), domestic animals (cats and dogs), equines (horses and foals), wildlife (rabbits, wild birds, shrews, raccoons, feral swine, ostriches, Kodiak bears, zebras, kangaroos, elephants, ibex, tamarin monkeys, and chimpanzees), and marine organisms (bivalve molluscs) (103,178,(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196). Many of these studies described differences in prevalence (particularly a decline with age), toxigenic status, antibiotic resistance, clonal lineage, and host susceptibility to disease, as well as differences in veterinary and agricultural practices (178,180).…”
Section: Animal Reservoirs and Zoonotic Potentialmentioning
confidence: 99%
“…19 Multidrug-resistant bacteria Multidrug-resistant bacteria of public health importance have been found in people and companion animals. 20,21 Cross-sectional studies have shown pet owners to have a six-fold greater risk for colonization with extended-spectrum β-lactamase-producing Escherichia coli than people who do not own pets, 22 and pets owned by people with compromised immune systems are more likely to be colonized with Clostridium difficile than those owned by people with competent immune systems. 20 A similar increased risk was seen in dogs that visit human health care facilities, with acquisition of C. difficile and methicillin-resistant Staphylococcus aureus two to five times more common than in dogs involved in other interventions.…”
Section: 18mentioning
confidence: 99%
“…20,21 Cross-sectional studies have shown pet owners to have a six-fold greater risk for colonization with extended-spectrum β-lactamase-producing Escherichia coli than people who do not own pets, 22 and pets owned by people with compromised immune systems are more likely to be colonized with Clostridium difficile than those owned by people with competent immune systems. 20 A similar increased risk was seen in dogs that visit human health care facilities, with acquisition of C. difficile and methicillin-resistant Staphylococcus aureus two to five times more common than in dogs involved in other interventions. 21 The current thinking for these predominantly human pathogens is that people serve as the main reservoir, but that household pets become colonized or infected, thus serving as a secondary source for human infection.…”
Section: 18mentioning
confidence: 99%